Radical adult education practices in the squatted city Plaza Hotel - Lihtenvalner, Katja (AS. Andragoška spoznanja, 2022)
The article is set in the political, social, and economic context of Greece, where newly arrived refugees and migrants have ended up following the 2016 EU-Turkey agreement. The forcefully marginalised new arrivals found themselves trapped in a traditionally hostile migration environment. Greece was already struggling with severe neoliberal policies imposed by foreign lenders and accepted by domestic polit-ical elites, which have drastically affected the welfare state. In the politically and economically hectic times institutional racism and social exclusion became integrated into national migration policies. By conducting qualitative interviews, participation observation, and by exploring secondary sources, this article centres around a housing project which developed as a response to neoliberal hegemonic poli-cies. The findings show that educational initiatives lead to the building of counter-hegemonic commu-nity, provided the practices of solidarity and collective learning, and helped educate the general public.
Keywords: andragogika; begunci; človekove pravice; hegemonija; radikalno izobraževanje odraslih; solidarnost